2019
DOI: 10.26552/ems.2019.1.38-50
|View full text |Cite
|
Sign up to set email alerts
|

Strategic leadership and sustainability performance of small and medium enterprises

Abstract: The small-scale industry in Nigeria is considered to be an important element to the growth of the economy in contributing to the gross domestic products of the economy, and it has been of contention that strategic leadership has influenced and sustained the performance of small and medium enterprises. As such, the main objective of the study is to examine how the exercising of strategic leadership has influenced and sustained the performance of small and medium enterprises in Nigeria in terms of social impact.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…From the analysis conducted that the strength of this business is Using high quality and environmentally friendly materials, weakness The product is still new so not many people know about it, the opportunity of this business is More and more mothers are aware of their baby's skincare and threats from This business is that these are Competitors who are fast adopting technology. The implementation of strategic leadership in this study is in line with that carried out by Priadana (2021), Al Thani (2020 and Kowo (2019) when they said is strategic leadership has significant effect on the success of a company in acheving operational excellence…”
Section: Analysis Strategic Leadershipsupporting
confidence: 88%
“…From the analysis conducted that the strength of this business is Using high quality and environmentally friendly materials, weakness The product is still new so not many people know about it, the opportunity of this business is More and more mothers are aware of their baby's skincare and threats from This business is that these are Competitors who are fast adopting technology. The implementation of strategic leadership in this study is in line with that carried out by Priadana (2021), Al Thani (2020 and Kowo (2019) when they said is strategic leadership has significant effect on the success of a company in acheving operational excellence…”
Section: Analysis Strategic Leadershipsupporting
confidence: 88%
“…(6) shows that the F value for Absorptive as an independent variable =223.152, indicating that there is a significant relationship between Absorptive and organizational effectiveness(223.152>1). As it can be seen in table (8), the correlation analysis between capacity to change as a skill of self-leadership as a tangible resource to measure its influence on organizational effectiveness in small and medium businesses in Kurdistan region of Iraq. The finding revealed that the value of Pearson correlation (r= .698 **, p<0.01), this indicated that there is positive and strong correlation between capacity to change as self-leadership skill and sustainable competitive advantage.…”
Section: First Research Hypothesismentioning
confidence: 99%
“…Further, SMMEs did not put plans in place to groom, train and develop top managers. In the study by Kowe and Akinbola (2019) in Nigeria, it was found out that there is a significant influence of strategic planning on sustaining small and medium enterprises for profit performance and thus managers who sustain profitability performance are those that are strategic in planning. It followed therefore that return on investment depended upon the appropriateness of leadership practices in management.…”
Section: Leadership and Governance On Management Of Auto-garagesmentioning
confidence: 99%